THE PROPER MOTION OF SUNSPOTS UMBRA IN THE RISING PHASE OF CYCLE 24 - Permata, Kamila
The differential rotation is the difference in the rate of rotation of each latitude in the Sun indicating that the Sun is not a solid body. The differential rotation is the result of the interaction between rotation and convection and causes dynamo circulation that affects the cycle of solar activity. In this thesis, we measured the coordinates of 304 sunspots umbra as tracer in the rising phase of the solar cycle 24th to obtain the differential rotation equation. Coordinates of sunspots were measured using AIA images at a wavelength of 4500 Å from SDO (Solar Dynamic Observatory) with JHelioviewer software. The areas of sunspots were measured using HMI (Helioseismic Magnetic Imager) images from SDO with ImageJ software. From the measurement, we derived the differential rotation equation, the relation of sidereal rotation and area of sunspots umbra, the relation of sunspots umbra’s velocity and Zurich and McIntosh classification, the relation of sunspots umbra’s velocity and coronal hole, and the relation of sunspots umbra’s velocity and spotless days. The differential rotation equation obtained in this thesis is ? (B) = (14,27 ± 0,01) - (0,78 ± 0,10) sin2B (°/day). There is a difference between the differential rotation equation of northern and southern hemisphere that indicates the asymmetry between different hemispheres. We got the sidereal rotation of sunspots with area <5 mHem is 0,70% higher than sunspots with area > 15 mHem. For the relation between sunspots umbra’s velocity and Zurich classification, AB class (young sunspot) has the highest velocity, while H class (old sunspot) has the lowest velocity. For the penumbral class in McIntosh classification, x class (no penumbra) and r class (incomplete penumbra) has the largest latitudinal and longitudinal velocity. For the sunspot distribution in McIntosh classification, i class (intermediate) and c class (compact) has highest latitudinal and longitudinal velocity. The average of sunspot’s speed after the spotless days is higher than before spotless days. When the coronal hole is large, the activity of the sunspots is lower, indicated by the low sunspot’s speed when the coronal hole is small.